The influence of the internet environment on the professional burnout of students as the problem of the modern world - Vlasova, M. D. (Національний технічний університет "Харківський політехнічний інститут", 2020)
The materials processed and indicated in this article are intended to represent studying the problem of the influence of Internet sources on the occurrence of emotional burnout in the age group of students, whose psyche is daily influenced by emotionally depressing factors, which may be the reason for the appearance of their physical and emotional exhaustion.

Матеріали, оброблені та зазначені в цій статті, спрямовані на вивчення проблеми впливу Інтернет-джерел на виникнення емоційного вигорання у віковій групі студентів, на психіку яких щодня впливають емоційно пригнічуючи фактори, що може бути причиною появи в них фізичного та емоційного виснаження.
Вплив інтернет-середовища на професійне вигорання студентів як проблема сучасного світу
Keywords: internet; students; procrastination; Інтернет; студентство; прокрастинація